Exploring the Prevention and Treatment of Epilepsy based on the Theory of Ambrosia - Kan, Xiaoru; Cheng, Nan; Liu, Jinghan; Wang, Jiayue; Chen, Jun (Journal of Contemporary Medical Practice, 2024)
The theory of "Fu Xie" is one of the important theories in traditional Chinese medicine, which guides the prevention and treatment of many diseases, including epilepsy. Epilepsy is a common neurological disease with complex etiology and diverse clinical manifestations. According to the theory of "Fu Xie", epilepsy is caused by factors such as liver wind, phlegm turbidity, dampness evil, and fire heat. Therefore, the key to treating epilepsy is to clear these pathogenic factors and regulate the body's physiological functions such as Qi, blood, Yin, and Yang. In Chinese medicine treatment, drugs such as Chai Hu and Qing Pi can be used to regulate liver Qi and clear liver heat. Drugs such as Ban Xia and Zhi Shi can be used to clear heat, transform phlegm, and promote diuresis to eliminate phlegm turbidity. Drugs such as Qu Mai and Fu Ling can be used to strengthen the spleen, dispel dampness, and open the orifices to stop seizures. Drugs such as Huang Lian and Huang Qin can be used to clear heat, detoxify, nourish Yin, and reduce fire. The theory of "Fu Xie" has important guiding significance for the prevention and treatment of epilepsy, and can provide effective reference for clinical treatment.